Arthrospira platensis protein isolate for stabilization of fluid interfaces: Effect of physicochemical conditions and comparison to animal-based proteins. (March 2023) - Bertsch, Pascal; Böcker, Lukas; Palm, Ann-Sophie; Bergfreund, Jotam; Fischer, Peter; Mathys, Alexander
Abstract: Proteins from microalgae bear great potential to replace animal-based proteins in the human diet or as functional ingredients, such as interfacial stabilizers of emulsions and foams. To establish microalgae proteins as viable alternative, it is critical to understand the effect of physicochemical conditions on their adsorption behavior and interfacial network formation. Here, we extract a protein isolate from the cyanobacterium Arthrospira platensis and investigate its interfacial performance in a broad range of concentration, pH, ionic strength, and at oils with altering polarity. Compared to reference conditions (pH 7, 20 mM ionic strength) adsorption is accelerated at intermediate pH 5 due to decreased electrostatic repulsion but decelerated at the isolate's isoelectric point (pI = 3.5) due to protein aggregation. Conversely, a lower protein charge at the pI favors the formation of strong viscoelastic interfacial layers. Increased ionic charge screening results in faster adsorption and increased interfacial viscoelasticity. Adsorption at oils with varying polarity revealed that A. platensis isolate adsorption and viscoelasticity is largely independent of oil polarity and is only impeded at extremely polar oils. Based on this adsorption behavior, we conclude that the obtained isolate is a mixture of protein fractions with varying structural stability. Ultimately, we compare the interfacial performance of the A. platensis isolate with fractionated animal-based proteins. The A. platensis isolate is more efficient at reducing interface tension compared to the commonly employed β-lactoglobulin, lysozyme, albumin, or casein. Hence, A. platensis protein isolate is an efficient interfacial stabilizer in a broad range of physicochemical properties which outperforms many currently used animal-based proteins. Graphical abstract: Image 1 Highlights: Improved protein isolation protocol from A. platensis biomass. Investigation of protein isolate adsorption kinetics and interfacial viscoelasticity. Detailed study on effects of pH, ionic strength, and oil polarity. Insights on A. platensis isolate protein structures. Interfacial performance compared to animal-based proteins.